2007
DOI: 10.1177/1073191106295914
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the PAI and the MMPI-2 for Discriminating PTSD, Depression, and Social Phobia in Trauma-Exposed College Students

Abstract: This study investigated the Minnesota Multiphasic Personality Inventory-Revised (MMPI-2; Butcher, Dahlstrom, Graham, Tellegen, & Kaemmer, 1989) and the Personality Assessment Inventory (PAI; Morey, 1991) with regard to each instrument's utility for discriminating post-traumatic stress disorder (PTSD) from depression and social phobia in a sample of college students with mixed civilian trauma exposure. Participants were 90 trauma-exposed undergraduates (16 male, 74 female) classified into one of four groups: PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Approximately two thirds of college students report trauma exposure and approximately nine percent endorse symptoms consistent with a posttraumatic stress disorder (PTSD) diagnosis (Read, Ouimette, White, Colder, & Farrow, 2011; Smyth, Hockemeyer, Heron, Wonderlich, & Pennebaker, 2008). Many more students report post-trauma symptomatology which, despite falling below somewhat arbitrary diagnostic thresholds, is impairing nonetheless (McDevitt-Murphy et al, 2007; Read et al, 2011; Smyth et al, 2008). Trauma and posttraumatic stress (PTSD) have been linked to harmful or hazardous drinking in young adults (Kaysen et al, 2014; Read et al, 2012; Simpson et al, 2014), and may be among the factors that account for non-resolution of problem drinking as young adults transition through their third decade of life.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately two thirds of college students report trauma exposure and approximately nine percent endorse symptoms consistent with a posttraumatic stress disorder (PTSD) diagnosis (Read, Ouimette, White, Colder, & Farrow, 2011; Smyth, Hockemeyer, Heron, Wonderlich, & Pennebaker, 2008). Many more students report post-trauma symptomatology which, despite falling below somewhat arbitrary diagnostic thresholds, is impairing nonetheless (McDevitt-Murphy et al, 2007; Read et al, 2011; Smyth et al, 2008). Trauma and posttraumatic stress (PTSD) have been linked to harmful or hazardous drinking in young adults (Kaysen et al, 2014; Read et al, 2012; Simpson et al, 2014), and may be among the factors that account for non-resolution of problem drinking as young adults transition through their third decade of life.…”
Section: Introductionmentioning
confidence: 99%
“…It has shown growing applicability in clinical populations, including borderline pathology (Stein, Pinsker-Aspen, & Hilsenroth, 2007), alcohol dependency (Schinka, 1995), forensics (Edens & Ruiz, 2008), posttraumatic stress disorder (McDevitt-Murphy, Weathers, Flood, Eakin, & Benson, 2007), and individuals with head injuries (Demakis et al, 2007;Kurtz, Shealy, & Putnam, 2007). Both the MMPI and PAI are multidimensional, have sound psychometric properties, and share many commonalities in the clinical symptoms assessed, including scales tapping symptoms of depression, anxiety, somatic focus, paranoia, mania, antisocial features, and schizophrenia.…”
mentioning
confidence: 98%
“…Results showed that hyperarousal and avoidance symptoms were the best predictor of emotional numbing (Flack, Milanak, & Kimble, 2005). College students with PTSD report drinking to higher intoxication levels than college students without PTSD (McDevitt-Murphy, Weathers, Flood, Eakin, & Benson, 2007).…”
Section: Focusing On Young Adultsmentioning
confidence: 97%